AN APPLICATION OF COMPARISON CRITERIA TO FRACTIONAL SPECTRAL PROBLEM HAVING COULOMB POTENTIAL - Bas, Erdal; Metin Turk, Funda (Vinca Inst Nuclear Sci, 2018)
In this study, the zeros of eigenfunctions of spectral theory are considered in fractional Sturm-Liouville problem. The 1st and 2nd comparison theorems for fractional Sturm-Liouville equation with boundary condition and their proofs are given. In this way, our new approximation will contribute to construct fractional Sturm-Liouville theory. Also, its an application is given in case of Coulomb potential and the results are presented by a symbolic graph.
Keywords: thermal conduction; angular momentum; Coulomb potential; energy equation; Sturm-Liouville; Schroedinger equation